2015
DOI: 10.1007/s12185-015-1850-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) after treatment for Hodgkin’s lymphoma

Abstract: Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) is a rare central nervous system (CNS) disorder with distinct radiological features. However, CLIPPERS may mimic CNS lymphoma, and several cases in which CLIPPERS occurred premonitory to CNS lymphoma have been reported. We report a 31-year-old man presenting with progressive gait ataxia and the characteristic MRI features of CLIPPERS. He was diagnosed with stage II Hodgkin's lymphoma at the age of 15, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Interestingly, one report described a case of CLIPPERS in which EBV infection led to a dramatic elevation of the EBV DNA level in the CSF, while a PCR failed to detect EBV in the serum and no EBV involvement was detected in a brain biopsy specimen using in situ hybridization of EBER (19). Moreover, several reported cases of CLIPPERS have occurred in patients with immunosuppressive backgrounds, such as patients with history of chemotherapy or steroid use, which may be involved in EBV reactivation (16, 19, 20). Given the features of our case and the reported cases, EBV infection or reactivation in the CNS may be associated with the core features of CLIPPERS (i.e., punctate “peppering” enhanced lesions or perivascular T-cell infiltration), which are also observed in cases of EBV+ DLBCL or CNS-LYG.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one report described a case of CLIPPERS in which EBV infection led to a dramatic elevation of the EBV DNA level in the CSF, while a PCR failed to detect EBV in the serum and no EBV involvement was detected in a brain biopsy specimen using in situ hybridization of EBER (19). Moreover, several reported cases of CLIPPERS have occurred in patients with immunosuppressive backgrounds, such as patients with history of chemotherapy or steroid use, which may be involved in EBV reactivation (16, 19, 20). Given the features of our case and the reported cases, EBV infection or reactivation in the CNS may be associated with the core features of CLIPPERS (i.e., punctate “peppering” enhanced lesions or perivascular T-cell infiltration), which are also observed in cases of EBV+ DLBCL or CNS-LYG.…”
Section: Discussionmentioning
confidence: 99%
“…[7] However, findings in brain biopsy showed no evidence of CNS lymphoma since the Ki67 labeling index, which is strictly associated with cell proliferation, was 10%. Manual CSF cytology and hematologic investigations did not reveal any malignant cells either.…”
Section: Discussionmentioning
confidence: 99%
“…Ortega et al [11] described a patient with MS who developed CLIPPERS shortly after natalizumab withdrawal. Mashima et al [12] reported a case who developed CLIPPERS after treatment for Hodgkin's lymphoma. Wang et al [13] reported a case of CLIPPERS following herpes zoster infection.…”
Section: Discussionmentioning
confidence: 99%